Historical Roots of the Formation of Concepts of Professions in Preschool Children (Eurasian Journal of Learning and Academic Teaching, 2022)
This article describes the historical roots of the formation of ideas about professions among preschoolers. The article also summarizes opinions on the coverage of vocational education in folk oral and written sources